2016
DOI: 10.5902/2236117019719
|View full text |Cite
|
Sign up to set email alerts
|

Análise de superação de dormência de sementes de Leucaena leucocephala e desenvolvimento inicial de plântulas

Abstract: Leucaena is an exotic fabaceae that has a much diversified utilization, highlighting the reforesting of degraded areas for the erosion control. For presenting a quite slow growth, the success of its cultivation is related to the sowing and seed emergency, that consequently require the utilization of methods of overcoming physic dormancy in seed germination to succeed. This paper aimed evaluates the effect of methods of overcoming dormancy on seed germination and on initial development of leucaena plantlet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
2
0
7
Order By: Relevance
“…No caso da leucena, cuja dormência é primária, do tipo exógena, devido à impermeabilidade do tegumento, os métodos a serem usados na superação da dormência deverão promover aberturas no tegumento, permitindo sua embebição, como ocorre com a escarificação mecânica, tratamento químico com substâncias ácidas (ácido sulfúrico, ácido clorídrico) ou básicas (hidróxido de sódio), tratamento térmico com imersão em água quente, imersão em água fria por um tempo maior, tratamento com solventes (éter, álcool, acetona) e incisão com lâmina ou estilete. (ALVES et al, 2007;MARIANO et al, 2016).…”
Section: Introductionunclassified
“…No caso da leucena, cuja dormência é primária, do tipo exógena, devido à impermeabilidade do tegumento, os métodos a serem usados na superação da dormência deverão promover aberturas no tegumento, permitindo sua embebição, como ocorre com a escarificação mecânica, tratamento químico com substâncias ácidas (ácido sulfúrico, ácido clorídrico) ou básicas (hidróxido de sódio), tratamento térmico com imersão em água quente, imersão em água fria por um tempo maior, tratamento com solventes (éter, álcool, acetona) e incisão com lâmina ou estilete. (ALVES et al, 2007;MARIANO et al, 2016).…”
Section: Introductionunclassified
“…Tratamentos Para Mariano et al (2016) verificaram que em sementes de leucena a altura de plântulas não obteve diferença significativa entre escarificação com lixa n 0 100, imersão em ácido sulfúrico e, imersão em água a 80 0 C, mas, encontraram o menor valor para esta característica no tratamento testemunha, fato que corrobora os resultados encontrados nesse experimento. Provavelmente grande parte da energia utilizada pela semente para romper o tegumento natural devido à dormência em sementes não tratadas (testemunha) tenha sido maior, quando comparada a energia usada nas sementes submetidas aos demais tratamentos, sendo assim, no momento do crescimento a plântula não obteve energia suficiente para expressar sua altura adequada.…”
Section: Resultsunclassified
“…It was observed that the germination rate, length and dry mass of seedlings increased as the substrate concentrations increased, evidencing that the potassium nitrate and salt stress in L. leucocephala seeds (Figs. 1 B, C and D) This is because the mechanism of action of potassium nitrate acts on the reception of electrons, reducing the nitrite form inside the seeds, reoxidizing the NADPH and increasing the availability of NADP which reduces the dehydrogenases in the pentose phosphate cycle, helping to overcome seed dormancy [3]. In addition to being an excellent growth promoter of seedlings, potassium nitrate can also act to maintain balance in plant cells, promoting respiration and metabolism of carbohydrates [23].…”
Section: Resultsmentioning
confidence: 99%
“…Sowing can be done either by seedlings or directly on the site [2]. However, sowing in saline soils in regions with a low frequency of rainfall results in slow and irregular emergence, with direct reflexes on the seedling development [3].…”
Section: Introductionmentioning
confidence: 99%